Proposing an Optimized Cost-Effective Data Carrier Mechanism for Smart Contracts and Transactions in Blockchain with ACO Algorithm - Sabbagh, Parisa (Advances in Social Sciences Research Journal, 2021)
In this article, a new optimal cost-effective data carrier architecture for smart contracts in the blockchain-enabled IoT environment proposed. This method requires communication with external off-chain data. Three steps consist of this model such as Mission Manager, Task Publisher, and Worker which formulated with the ACO algorithm. Based on this method, some of the best solutions for filtering smart contract events and decoding event logs to fit different requirements are presented adequately. The proposed system is designed to minimize contract deployment costs and monitor contract events without subscribing to any filter at the Ethereum node. In the evaluation, we show that it will save about 21USD deployment costs for average by our data carrier system.